Typification of the production system of snuff (iNicotiana tabacum/i) in the Guanenta province, Santander department, Colombia (2017)
In the province of Guanenta (Santander), lack of technical assistance received by producers is one of the main obstacles to the production of snuff. The objective of this research was to characterize the snuff production systems in the province, considering technical, socioeconomic and environmental variables. The sample was determined from census by producers supplied by Coltabaco, using stratified random sampling; the data were processed by multiple correspondence analysis. The results are shown as discriminant variables: type of snuff, the percentage of sharecropping, type of leaf curing, implementation of irrigation system, development of alternative crops, crops rotation and membership of producers to associations. Four types of production systems were found: i) conventional - snuff type burley, ii) technified - snuff type burley, iii) conventional alternative - snuff type burley, iv) conventional - snuff type black. Finally and aiming improve the production of snuff, this study propose improvement actions for technical assistance programs received by producers, alternatives for access improvement and availability of water.